A Sakta Method for Comparative Theology: Upside Down, Inside Out - Rodrigues, Pravina (Lexington Books, 2023)
A Śākta Method for Comparative Theology: Upside-Down, Inside-Out offers a Śākta thealogy of religions and a Śākta anti-method, method, and a-method for comparative theology. For Śāktas, the thread of religious diversity is part of the rich tapestry of cosmological, topographical, environmental, and bio-diversity, which is the Goddess’ collective (samaṣṭi) and individuated (vyaṣṭi) forms. Śākta religious diversity is "complex, layered, and paradoxical, allowing ontological similarities, ontological differences, and irreducibility." A Śākta thealogy of religious diversity transcends humans and the borders of religion, politics, society, and speciesism.